Adapting the revised prenatal coping inventory (NuPCI) for use in a Spanish population - L. Lorén-Guerrero; A. Gascón-Catalán; M. A. Romero-Cardiel (Taylor & Francis Group, 2018)
Objective: To adapt the Revised Prenatal Coping Inventory (NuPCI) for the evaluation of prenatal stress coping strategies utilised by Spanish women. Methods: A cross-sectional study was performed to evaluate the psychometric properties of NuPCI adapted for a Spanish population. Two hundred and sixty one puerperium women completed the NuPCI at the time of discharge after childbirth. Instrument construct validity was evaluated using subscale item correlations. Internal consistency was assessed using Cronbach's α test. Results: Items from each subscale (Preparation, Avoidance and Spiritual - Positive Coping) were significantly correlated with the global result (p < .001). The internal reliability of the NuPCI demonstrated suitable values for each of the three coping strategies (α > 0.7). The most frequently used coping strategy was Preparation and the least used was Avoidance. Utilisation of the coping strategies with Preparation decreased with increasing parity (p = .002) and greater prenatal stress was associated with increased use of the Avoidance coping strategy (p < .001). Conclusions: The NuPCI adapted for Spanish women demonstrates good psychometric properties for evaluating the three types of prenatal stress coping strategies: Preparation, Avoidance and Spiritual - Positive Coping. Results were similar to those presented by the instrument in its English language version.